The Relationship between Logistic Capability and Logistic Performance among Logistic Industry in Johor - Pang, Pang Yong; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2025)
The logistics sector is crucial to Malaysia’s economy, particularly in Johor, which has made significant investments in infrastructure supporting logistics. Despite this, the logistic industry continues to face challenges such as delivery delays, transportation capacity shortages, and inadequate infrastructure, which hinder their performance. Therefore, the purpose of this study is to identify the level of logistic performance, examine the level of logistic capability, and find out the relationship between logistic capability and logistic performance among the logistic industry in Johor. The quantitative research method was employed in this study, using an online survey questionnaire distributed to 162 managerial level employees of Third-Party Logistics (3PL) providers in Johor, the valid responses were collected from 135 managerial level employees. Descriptive analysis and Spearman’s correlation analysis were conducted using SPSS software. The findings reveal that both logistics capability and logistics performance are rated highly among 3PL providers, with key dimensions of capability which are innovation capability, responsiveness capability, and flexibility capability showing significant influence. The correlation analysis indicates a strong positive relationship (r = 0.662) between logistics capability and performance, showed that logistics capability had a positive influence on logistics performance. These results offer valuable insights for logistics firms in Johor to enhance their operational efficiency and competitive advantage.